User experience in product design and development: Perspectives and strategies - Geena Sandra Codfrey; Aslina Baharum; Nurul Hidayah Mat Zain; Muhammad Omar; Farhana Diana Deris (Auricle Technologies, 2022)
Product design and development can be an overwhelming process especially for those who want to produce a product that is usable for most people. Designers and developers are always finding ways to involve the user in the production of a product. The objective of this study is to provide insight into the users' involvement and to determine strategies involving users in product design and development. Systematic review with the analysis of research articles has been done to achieve the objective. Results show the proposed framework for user experience in product design and development needed to involve users’ perspectives and strategies for high-quality products. User perspective on the product can give valuable user experience information. For the designers to have good perspectives, a good strategy must be created to obtain the user experience information from users.